Investigation of the relative abundances of single-core and multicore compounds in asphaltenes by using high-resolution in-source collision-activated dissociation and medium-energy collision-activated dissociation mass spectrometry with statistical considerations. (15th June 2019) - Dong, Xueming; Zhang, Yuyang; Milton, Jacob; Yerabolu, Ravikiran; Easterling, Leah; Kenttämaa, Hilkka I.
Graphical abstract: Abstract: Asphaltenes cause multiple problems in the petroleum industry, such as clogging crude oil transportation pipelines and fouling catalysts. Characterization of the structures of the compounds in asphaltenes is essential for addressing these problems. Two main categories of asphaltene molecular structures, single-core (island) and multicore (archipelago), have been agreed upon. However, their relative abundances in asphaltenes have been debated for decades. This may be partially due to the fact that many mass spectrometry studies carried out in both academia and industry make conclusions for the entire asphaltene sample based on information derived from a group of ionized asphaltenes with m / z values ranging from one up to ten. This approach makes the unvalidated assumption that the relative abundances of single- and multicore compounds are uniform within the entire sample. In this study, medium-energy collision-activated dissociation (MCAD) in a linear quadrupole ion trap/orbitrap high-resolution mass spectrometer was employed to explore the structures of asphaltene molecular ions with m / z values in the ranges of 350 ± 10, 450 ± 10, 550 ± 10 and 650 ± 10. The ions studied displayed different extents of decrease in their weighted average ring and double bond equivalence (RDBE) values when undergoing dissociation, suggesting that the abundances of single-core and multicore compounds are not uniform within the entire asphaltene samples. Therefore, traditional mass spectrometry approaches used to determine the relative abundances of single- and multicore asphaltene compounds may suffer from a sampling bias. However, in-source collision-activated dissociation (IS-CAD) is not susceptible to sampling bias because no ion selection is involved.